A Review Article of the Pragmatics Competence in EFL Learning Context - Amaliah, Amaliah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Cross-cultural communication requires pragmatics. Pragmatics is